THE POISON DIARY OF 1995 Part - 3 - Abd Razak, Dzulkifli (1996)
The last two months of 1995 were not spared it share of major poisoning incidents. The year came to a close with a dramatic reminder that poisons constitute a real and immediate threat to us all. November The cabinet approved new terms to allow a private company a 15year concession to run the country's first toxic waste management plant costing RM 375 million. Industries accumulated about 125,000 tonnes of toxic waste between 19871994, all waiting to be disposed at the new plant. Meanwhile, the Johor State Economic Development Corporation, in a joint venture with two Japanese firms, will build a plant to treat toxic industrial waste. In Kemaman, 300odd drums of lubricating oil were dumped near a housing estate. The dumping took place because the company lacked storage place. Under the Environmental Quality (Scheduled Waste) Regulations 1989, the onus is on the waste generator to notify the DOE every three months on the amount of waste generated and how the materials were stored or treated.